E-Health: Biomedical instrumentation with Arduino. Issue 1 (July 2017) - Puente, S.T.; Úbeda, A.; Torres, F
Abstract: This contribution describes the planning and the development of laboratory activities for an introduction to biomedical system instrumentation, as well as some experiences and results obtained from them. The activities have been applied in the course "Systems and Instruments Foundations", during the academic year 2016-17. This course is scheduled in the second year of the novel Health Information Technology Degree offered by the University of Alicante. Teaching biomedical instrumentation from the point of view of engineering to students that have little medical and engineering background is a complex task. Laboratory practices proposed are presented in this paper, which is based on Arduino and e-Health shield to teach biomedical concepts. A project-based learning methodology is used in the laboratory sessions, where students have to accomplish a project at the end of the semester.